Characterization of collagen and its hydrolysate from southern bluefin tuna skin and their potencies as DPP-IV inhibitors - Erwina Safitri; Olivia H. Kuziel; Takeshi Nagai; Masataka Saito (Food Chemistry Advances)
Collagen-derived peptides have been gaining interest due to their potential to act as DPP-IV inhibitors, which are considered to have antidiabetic effects. This study focused on extracting type I collagen from discarded southern bluefin tuna skin, confirming its structure and properties, and then measuring the ability of its hydrolysates to act as DPP-IV inhibitors. First, type I collagen was purified from southern bluefin tuna skin, and the constituent subunit was found to contain the α3(I) chain. Next, enzymatic hydrolysates were prepared, and their DPP-IV inhibitory activity measurements were examined and compared. Collagenase hydrolysate showed the highest DPP-IV inhibitory activity (71.8 ± 0.3 %), and considering digestive degradation, collagenase-pepsin-trypsin hydrolysate was prepared and separated into fractions via anion exchange chromatography, cartridge column, and HPLC. Notably, the 70 % methanol eluted fraction separated via cartridge column was found to have an IC50 of 0.26 ± 0.01 mg/ml. Subsequently, a novel peptide GPSGGGYDV with the highest DPP-IV inhibitory activity (IC50 value 82±0.0 µM) was purified from this fraction and found to be a competitive inhibitor of DPP-IV. This is the first study to investigate the DPP-IV inhibitory potential of type I collagen hydrolysate from southern bluefin tuna.